2017
DOI: 10.1128/jvi.01234-17
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for Interleukin-17 in Enhancing Type 1 Helper T Cell Immunity in the Female Genital Tract following Mucosal Herpes Simplex Virus 2 Vaccination

Abstract: It is well established that interferon gamma (IFN-γ) production by CD4 T cells is critical for antiviral immunity against herpes simplex virus 2 (HSV-2) genital infection. However, the role of interleukin-17A (IL-17A) production by CD4 T cells in HSV-2 antiviral immunity is yet to be elucidated. Here we demonstrate that IL-17A plays an important role in enhancing antiviral T helper type 1 (T1) responses in the female genital tract (FGT) and is essential for effective protection conferred by HSV-2 vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
5
39
1
1
Order By: Relevance
“…Our results showed that IL‐17A knockout might not influence the clearance of HSV virus (). Bagri and colleges also reported that HSV viral titres in IL‐17A ‐/‐ mice were not significantly different from that of WT mice during genital HSV infection . However, neither our results nor Bagri's work were actual measurements from the lung.…”
Section: Discussioncontrasting
confidence: 75%
“…Our results showed that IL‐17A knockout might not influence the clearance of HSV virus (). Bagri and colleges also reported that HSV viral titres in IL‐17A ‐/‐ mice were not significantly different from that of WT mice during genital HSV infection . However, neither our results nor Bagri's work were actual measurements from the lung.…”
Section: Discussioncontrasting
confidence: 75%
“…13 IL-17 has been shown to be important for establishing a Th1 response in a murine model of genital Chlamydia infection and in the Herpes simplex virus 2 animal model. 13,19,20 Whether IL-17 plays a similar role during a C.t. infection remains to be shown.…”
Section: Discussionmentioning
confidence: 99%
“…This is interesting since previous data suggested that Th17 T cells may have a role in inducing pathology. [12][13][14][15][16][17][18][19][20] As the Th17 T cell cytokine profile differed markedly from the Th17 cytokine profile in nonvaccinated/infected animals (that developed pathology), it could be speculated that only certain Th17 T cell subsets are associated with pathology, and that a Th17-inducing vaccine can prevent induction of the pathology-inducing Th17 T cells that are normally induced by the infection itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much like circulating CD4 + memory T-cells, studies of tissue-resident lymphocytes have predominantly focused on CD8 + T RM due to the heterogeneity of CD4 + memory T-cells and the existing gaps in knowledge regarding mechanisms governing memory CD4 + T-cell formation. Nevertheless, recent studies have highlighted a prominent population of long-lived CD4 + T-cells within many nonlymphoid tissues, including the lungs, 36,[49][50][51][52][53][54][55][56][57] small intestine (SI), 12,18,[58][59][60] skin, 15,[61][62][63][64] and female reproductive tract (FRT) 18,65,66 (Fig. 2).…”
Section: Tissue-resident Cd4 + Memory T-cellsmentioning
confidence: 99%